Causal relationships between the gut microbiota, inflammatory cytokines, and alcoholic liver disease: a Mendelian randomization analysis - Li, Shanzheng; Zhou, Cheng; Liu, Tong; Zhang, Lihui; Liu, Sutong; Zhao, Qing; Liu, Jiangkai; Zhao, Wenxia (Frontiers in Endocrinology, 2024)
Objective Previous studies have suggested a potential association between gut microbiota and the development of alcohol-related liver disease (ALD). However, the causal relationship between gut microbiota and ALD, as well as the role of inflammatory cytokines as mediators, remains unclear. This study aims to explore the causal relationship between gut microbiota and ALD using Mendelian randomization (MR) methods, and to analyze the mediating role of inflammatory cytokines. Methods Gut microbiota, 91 inflammatory cytokines, and ALD were identified from summary data of large-scale genome-wide association studies (GWAS). MR was employed to investigate the causal relationship between gut microbiota, cytokines, and ALD, with the inverse variance-weighted method (IVW) as the primary statistical approach. Additionally, we examined whether inflammatory cytokines act as mediating factors in the pathway from gut microbiota to ALD. Results The IVW results confirmed two positive and one negative causal effect between genetic liability in the gut microbiota and ALD. Escherichia coli (P= 0.003) was identified as a protective factor for ALD, while Roseburia hominis (P=0.023) and Family Porphyromonadaceae (P=0.038) were identified as risk factors for ALD. Furthermore, there were five positive and two negative causal effects between inflammatory cytokines and ALD, with CUB domain-containing protein 1 (P= 0.035), Macrophage colony-stimulating factor 1 (P=0.047), Cystatin D (P = 0.035), Fractalkine (P=0.000000038), Monocyte chemoattractant protein-1 (P=0.004) positively associated with ALD onset. CD40L receptor (P= 0.044) and Leukemia inhibitory factor (P = 0.024) exhibited protective effects against ALD. Mediation MR analysis indicated that CUB domain-containing protein 1 (mediation proportion=1.6%, P=0.035), Cystatin D (mediation proportion=1.5%, P=0.012), and Monocyte chemoattractant protein-1 (mediation proportion=3.3%, P=0.005) mediated the causal effect of Roseburia hominis on ALD. Conclusion In conclusion, our study supports a causal relationship among gut microbiota, inflammatory cytokines and ALD, with inflammatory cytokines potentially acting as mediating factors in the pathway from gut microbiota to ALD.